Screening of the active Ingredients in Huanglian Jiedu decoction through amide bond-Immobilized magnetic nanoparticle-assisted cell membrane chromatography - Liao, Fengyun; He, Dongmei; Vong, Chi Teng; Wang, Lisheng; Chen, Zhangmei; Zhang, Tiejun; Luo, Hua; Wang, Yitao (Frontiers in Pharmacology, 2022)
Introduction: The Huanglian Jiedu decoction (HLJDD) is a Chinese herbal formula that exerts neuroprotective effects by alleviating oxidative stress injuries and may potentially be prescribed for treating Alzheimer’s disease; however, its active ingredients have not yet been identified. Cell membrane chromatography is a high-throughput method for screening active ingredients, but traditional cell membrane chromatography requires multiple centrifugation steps, which affects its separation efficiency. Magnetic nanoparticles are unparalleled in solid-liquid separation and can overcome the shortcomings of traditional cell membrane chromatography. Methods: In this study, the neuroprotective effects of the components of HLJDD were screened through a novel magnetic nanoparticle-assisted cell membrane chromatography method. Magnetic nanoparticles and cell membranes were stably immobilized by amide bonds. Magnetic bead (MB)-immobilized cell membranes of HT-22 cells were incubated with the HLJDD extract to isolate specific binding components. The specific binding components were then identified by ultraperformance liquid chromatography (UPLC)—Orbitrap Fusion Tribrid MS after solid-phase extraction. The bioactivity of these components was analyzed in an HT-22 cellular model of glutamate-induced injury. Results and Discussion: The preparation method of the composite of cell membrane and MBs has the advantages of simple preparation and no introduction of toxic organic reagents. MBs not only provide support for cell membranes, but also greatly improve the separation efficiency compared with traditional cell membrane chromatography. Fifteen of these components were found to specifically bind to the cell membranes, and seven of them were confirmed to reduce varying degrees of glutamate-induced toxicity in HT-22 cells. In conclusion, our findings suggest that the amide bond-based immobilization of magnetic nanoparticles on cell membranes, along with solid-phase extraction and UPLC, is an effective method for isolating and discovering the bioactive components of traditional Chinese medicines.